Effects of coronavirus disease on tourism business and employment in eight selected operators in Victoria Falls, Zimbabwe - Moment Bhebhe (United Nations Ecoomic Commission for Africa, 2022)
The global proliferation of the coronavirus disease (COVID-19) pandemic has been unprecedented, with far-reaching implications for the world. As nations began to grapple with its untold effects in March 2020, global tourism succumbed to an unusual and implausible new reality. Most parts of the world, including Zimbabwe, imposed international and domestic travel bans and restrictions in order to prevent the spread of the virus, believed to have originated in China in December 2019. Victoria Falls, top tourism resort in Zimbabwe, submitted to the inevitable. The present paper explores the effects of COVID-19 on the tourism business and employment in Victoria Falls, using selected tourism operators. The impacts of a pandemic are never universal and should be studied in particular contexts. The findings reveal that the COVID-19 lockdown measures imposed by the Government of Zimbabwe more than a year ago heralded the worst performance of the sector. Operating capacities reduced to inconceivable levels and constrained the capacity operators to honour statutory obligations and maintain commitment to corporate social responsibilities. The requirement for operators to equip themselves with COVID-19 health-care supplies – an unforeseen expense – exacerbated business vulnerability. As business uncertainty remained high, and to save businesses, operators were forced to implement labour cost reduction measures such as job cuts, reduced working hours, unpaid leave and reduced salaries. Effective containment of the COVID-19 pandemic will significantly alleviate the distress experienced by the tourism industry